Penerapan Terapi Bermain Mewarnai Pada Anak Prasekolah Terhadap Kecemasan Akibat Hospitalisasi di RS PKU Muhammadiyah Karanganyar - Belinda Ayu Dewanti; Maryatun Maryatun (JURNAL RISET RUMPUN ILMU KESEHATAN, 2023)
Hospitalization is a form of stressor in children that lasts as long as the child is hospitalized, hospitalization becomes a crisis that must be faced by children. Feelings of anxiety are the impact of hospitalization experienced by pre-school children. This impact has the risk of interfering with child development and the healing process in children. To reduce children's anxiety, we need a media that can express anxiety, one of which is play therapy. Forms of games that are suitable for children aged 3-6 years are coloring pictures. The purpose of this application is to find out the results of applying play therapy to reducing anxiety due to hospitalization. The application method was carried out using a case study descriptive method to 3 respondents and the coloring play therapy was carried out once in 30 minutes. The results of the application that has been carried out are a decrease in anxiety due to hospitalization. The conclusion in this study is that coloring play therapy can be used as a technique to reduce feelings of anxiety in preschool children due to hospitalization.